STRATEGI PEMBELAJARAN BERBASIS KEARIFAN LOKAL DALAM MEMBENTUK KARAKTER RELIGIUS PESERTA DIDIK DI SMAN 9 TANA TORAJA - Paembonan, Fadli; Burhanuddin, Muh Azhar; A. Natsir, Andi Fadhilah; Surani; Hasan, Salim; Wahab, Abdul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine a local wisdom-based learning strategy for shaping the religious character of Grade XI students at SMAN 9 Tana Toraja and to assess the students' religious character following the implementation of this strategy. The study employs a qualitative approach with a descriptive research design. The research subjects consist of the Islamic Religious Education teacher and Grade XI students at SMAN 9 Tana Toraja. Data collection techniques include observation, interviews, and documentation. Data analysis involves data reduction, data presentation, and drawing conclusions with verification. Data validity is ensured through source and technique triangulation. The results indicate that the local wisdom-based learning strategy is implemented by integrating Tana Toraja cultural values ​​into the Islamic Religious Education learning process. The teacher connects the learning material to the students' daily lives and uses values ​​such as togetherness, mutual cooperation (*gotong royong*), politeness, mutual respect, caring, and responsibility as examples during instruction. This strategy renders learning more contextual and helps students understand the connection between religious values ​​and their socio-cultural lives. The students' religious character is reflected in habits such as praying before and after lessons, participating in religious activities, and demonstrating honesty, discipline, responsibility, politeness, helpfulness, respect for teachers and peers, and appreciation for diversity. This character formation is supported by habituation, the teacher acting as a role model, the school environment, and the role of the family. Thus, the local wisdom-based learning strategy plays a role in fostering the religious character of students by integrating local cultural values ​​with the values ​​of Islamic Religious Education.